Informing public health policy through deliberative public engagement: Perceived impact on participants and citizen-government relations - Molster, C.; Potts, A.; McNamara, Beverley; Youngs, L.; Maxwell, S.; Dawkins, Hugh; O'Leary, Peter (Mary Ann Liebert, Inc. Publishers, 2013)
Background: Deliberative public engagement has been proposed for policy development, where issues are complex and there are diverse public perspectives and low awareness of competing issues. Scholars suggest a range of potential outcomes for citizens and government agencies from involvement in such processes. Few studies have examined outcomes from the perspective of citizen participants in deliberative processes. Aims: To examine participant perceptions of their involvement in and outcomes of a deliberative engagement exercise. Method: A case study using semistructured interviews was conducted with participants following a deliberative forum on biobanking. Results: From their involvement in the deliberative exercise, participants described transformations in their knowledge and beliefs about the policy issues. They reported being more informed to the extent of having confidence to educate others and effectively contribute to public policy development. They had developed greater trust in government policymakers who they believed would take reasonable account of their recommendations.Conclusion: We conclude that the participants were satisfied with the outcomes of the deliberative public engagement process and viewed it as an effective means of citizen involvement in public policy development. Particularly for citizens who participate in deliberative processes, such processes may promote active citizenship, empower citizens to undertake representative and educative roles, and improve relations between citizens and government agencies. Actions taken by policymakers subsequent to the deliberative exercise, whereby the majority of citizen recommendations were incorporated in the policy developed, may have contributed to participants holding sustained levels of trust in the commissioning government agency.